Influence of age on clinical presentation, diagnosis delay and outcome in pre-school children with acute appendicitis - Yasmine Lounis; Julie Hugo; Martine Demarche; Marie-Christine Seghaye (BMC, 2020)
Abstract Background Unusual clinical presentation of acute appendicitis in preschool children leads to misdiagnosis and complications. We aimed to analyze the influence of age on clinical presentation, laboratory findings and complications in preschool children with acute appendicitis. Methods From January 2012 until December 2017, 29 children younger than 6 years of age (median 50 months) with acute appendicitis were enrolled in this retrospective study. Patients were grouped according to their age: group 1: < 48 months (n = 13); group 2: > 48 months (n = 16), their clinical data, laboratory results and complications were compared. Results In group 1, duration of nausea and vomiting was longer, alteration of general state was more frequent and pain in the right fossa iliaca less frequent than in group 2 (p = 0.026, p = 0.000 and p = 0.029, respectively). Heart rate was higher in group 1 than in group 2 (p = 0.012). Leucocyte and polynuclear neutrophil counts were lower in group 1 than in group 2 (p = 0.028 and = 0.004, respectively) but C-reactive protein levels were not different between groups. In the whole cohort however, C-reactive protein at admission value correlated negatively with age (p = 0.025). Abdominal ultrasound allowed diagnosis in 19/29 patients (65.5%), without any difference between groups. Appendicular perforation was more frequent in group 1 than in group 2 (p = 0.003). Perforation was also related to longer hospital stay (p = 0.018). Peritonitis occurred in 21/29 (72%), post-operative ileus in 5/29 (17%) and sepsis in 4/29 (14%) patients without any difference between groups. In the whole cohort, hospital stay correlated negatively with age (p = 0.000). There was no mortality. Conclusions Among preschool children, those younger than 48 months present with longer duration of pre-admission symptoms indicating longer infection course than in older children. Altered general state and higher degree of tachycardia in the younger reflect higher systemic repercussions of the illness. Less specific abdominal pain and dissociation of the inflammatory markers with lower leucocyte- and neutrophil counts and higher C-reactive protein levels in the younger may contribute to further diagnosis delay and higher rate of perforation in these patients.